Healthy Living: Keep Track of Your Blood Pressure - Linda B. Bobroff; Leigh Ann Martin (EDIS, 2013)
Every time you take your blood pressure, write down the date and time, the blood pressure measurement, and where it was taken (home, doctor’s office, etc.). Not only that but include any comments your health care provider made and anything you would like to note, such as how you feel or medications you recently started or stopped. This 2-page fact sheet was written by Linda B. Bobroff and Leigh Ann Martin and published by the UF Department of Family Youth and Community Sciences, October 2013.